2004
DOI: 10.1001/archotol.130.7.875
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life for Patients Following Total Laryngectomy vs Chemoradiation for Laryngeal Preservation

Abstract: Background:The incorporation of chemotherapy and radiation, either sequentially or concurrently, has been increasingly used for organ preservation in patients with advanced laryngeal cancer. Traditional outcome measures of clinical response such as locoregional control and survival have been similar for patients treated with chemoradiotherapy and those treated with total laryngectomy (TL). The impact of concurrent chemoradiotherapy for laryngeal preservation on the overall quality of life (QOL) of patients has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
150
2
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(177 citation statements)
references
References 35 publications
11
150
2
14
Order By: Relevance
“…The treatment of laryngeal cancer can be morbid, causing impaired vocalization, dysphagia, aspiration, and cosmetic deformity [2][3][4][5][6][7][8] . The subsite (glottis, supraglottis, or subglottis) and extent of cancer determine the treatment options available 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of laryngeal cancer can be morbid, causing impaired vocalization, dysphagia, aspiration, and cosmetic deformity [2][3][4][5][6][7][8] . The subsite (glottis, supraglottis, or subglottis) and extent of cancer determine the treatment options available 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study group 13 demonstrated that there were only marginal differences on the Senses scale between partial laryngectomy (N 5 12) and total laryngectomy (N 5 11) patients who had recurring laryngeal carcinomas after having completed radiotherapy. Comparisons between chemoradiation and surgery-radiation (total laryngectomy with postoperative radiation therapy 2 ) showed that the QLQ-C30 could not differentiate well enough between the side effects of the 2 treatments. In contrast, the QLQ-H&N35 indicated differences in amount of coughing, use of painkillers, sensory disturbances (more prevalent in the surgery-radiation group), and dryness of mouth (more prevalent in the chemoradiation group).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Its psychometric characteristics were published for the first time in 1992. 6 In that study, the internal consis-tency of the QLQ-C30 scales ranged from 0.28 (Cognitive Functioning scale) to 0.90 (Global Health Status) (see Table 1).…”
mentioning
confidence: 99%
“…Studies that compare the quality of life of patients after primary radiochemotherapy (pRCT) with total laryngectomy come to different results: Some state that the quality of life after pRCT is better than after laryngectomy [127], [128] while others conclude that the quality of life is equal after both therapeutic procedures [129], [130].…”
Section: Quality Of Lifementioning
confidence: 99%